A hybrid phosphorus-acid fuel cell system incorporated with oxidative steam reforming of methanol (OSRM) reformer. (June 2020) - Chang, Cheng-Ping; Wu, Yen-Chih; Chen, Wei-Yen; Pan, Chin; Su, Yu-Chuan; Huang, Yuh-Jeen; Tseng, Fan-Gang
Abstract: In this paper, a phosphoric acid fuel cell integrated with reformer and evaporator is demonstrated. Oxidative steam reforming of methanol (OSRM) process is employed in this system in cooperated with a high efficient evaporator, and the reacted gas is sent into a phosphorus-acid fuel cell (PAFC) for direct power generation after surplus methanol/water filtration. The results show that the maximum power density of this hybrid system achieves 277 mW/cm 2 without CO2 removal, while it achieves 485 mW/cm 2 when employing pure hydrogen as the fuel. Graphical abstract: Image 1 Highlights: A phosphoric acid fuel cell integrated with reformer and evaporator is demonstrated. OSRM Reformer including a high efficient evaporator. The maximum power density of this system achieves 277 mW/cm 2 without CO2 removal.